MAXIMIZING EFFICIENT USE OF REMOTE SENSING IMAGERY FOR LAND AND SPATIAL PLANNING - Azarya, Rahmadhony Azarya Triwicaksana; Muhammad Nur Kamila Amrullah (Journal of Geography, Regional Planning and Development, 2024)
Now all over the world there is a shift in the learning paradigm towards increasingly modern learning, the problems faced in Indonesia are very different from those in other countries. The need to accelerate spatial planning is increasingly needed day by day, but the lack of use of high resolution satellite imagery (CSRT) is very minimal because many still prefer to use aerial photography, even though satellite imagery has now developed rapidly and has an accuracy of 0.5 meters/centi, to obtain The data that I will use, I use the Mendeley software platform, and also search for several scientific journals from existing websites. The results that I got from the research study that I wrote as stated above is the importance of maximizing the use and utilization of images. This scientific study can conclude that the use of satellite imagery is no less important than aerial photography which requires more time in the field, the use of satellite imagery is a way to obtain information about the earth's surface from a certain distance. The concept is simple: if you observe a landscape object but it is still unclear, change perspective by standing up to see the object more clearly.